Use of Artificial Intelligence Technology in Tax Management: Evaluation of The Principle of Transparency Within the Framework of International Legislation Provisions - Ayşegül Yücel; Burçin Bozdoğanoğlu (International Journal of Public Finance, 2025)
Artificial intelligence is a technology that has found its place in all areas of life with the digitalization process and is used in many fields of science and disciplines with its sub-techniques. Within this wide usage area, the services provided by public administrations have also been affected by artificial intelligence technology. The tax management structure formed by the taxpayer and the administration has also changed under the influence of artificial intelligence technology. Most transactions in tax management based on automated decision-making can provide many advantages to the administration and the taxpayer. However, the use of artificial intelligence models with a black box or an intricate coding structure in the taxation process may violate the principle of transparency and may result in damage to taxpayer rights. The aim of the study is the determination of the problems in ensuring transparency, which is a public principle, as a result of the use of artificial intelligence technology in tax management and the presentation of suggestions for this purpose. In this context, the study used the literature review method; considering the current international legislation provisions, concluded that a legal system that protects taxpayer rights should be organized in order to ensure transparency in the use of artificial intelligence technology.